Desenvolvimento e calibração de um mini-tanque evaporimétrico - Costa, Selso Vieira (2004)
The present work had as aim a development and calibration of a small evaporation pan comparing its evaporation with class A pan and its capability to estimate the reference evapotranspiration comparing it with the Penman-Monteith equation. This tool has the finality to facilitate the irrigation control, not being necessary to sample or to install equipment in the field, thus decreasing work and material acquisition costs. Also, is intention whit this apparatus to not loose data at rainy days as occurs with the standard one (class A pan), make easier its management and reach closest estimates to reference evapotranspiration calculate by standard equation (Penman-Monteith). The development had consisted in a comparison, with patterns, of different phases in witch had used different hem, drain and water level height. The calibration had done by the adjusting of the values of reference evapotranspiration done through pan coefficient determination (Kpsm) contrasting small pan evaporation with standard evapotranspiration. Obtained results show a no significant correlation between characteristic height and pan performing expressed by c coefficient in relation to evaporation and evapotranspiration. Considering the SM pan capacity in estimate the rain height, is possible to correlate its performing to hem rising. In height lines we can consider, as average, that comparing whit class A pan, to five days average, the performing account as good and to ten days average as very good according to CAMARGO & CENTELHAS (1997) classification. At the comparison between the SM pan and Penman-Monteith methods, also as average, can be consider to five days average a performing account classify as ordinary and for ten days average as good . In case of rainy estimative, the performing rises from ordinary to excellent with the skirt rising. The regression coefficients - a and b statically disagree from its patterns - zero and one as rain as evapotranspiration estimates, pointing the necessity of these values correction. Whether considered the relation between SM and class A pans, these coefficients do not disagree from one and zero to ten days average, however using five days averages, the linear coefficient became disagree from zero. To make this corrections, meanwhile, is necessary a bigger data period to have more confidence values. In short, to obtained data, the small pan was capable to estimate well the evaporation measured at class A pan and the occurred rain and reasonable the reference evapotranspiration in spite of correction necessity. More over can be concluded that characteristic heights do not influence at evaporation and evapotranpirations values, but it does at the rain. It is known, however, this data are partial and to infer definitely on this tool efficiency it is necessary lengthen the experiment for some years and had placed at other sites.